2012
DOI: 10.2494/photopolymer.25.481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PEFC Membrane based on Cross-linked PTFE by EB Grafting: Effect of Thickness for FC Performance

Abstract: The performance of a polymer electrolyte fuel cell (PEFC) was affected by the thickness of the thin proton exchange membrane (PEM). The PEMs with the different thickness were prepared by radiation induced grafting of styrene into the radiation-cross-linked polytetrafluoroethylene (RX-PTFE) membrane prepared from PTFE dispersion, and then sulfonated. The wet thicknesses of the obtained thin PEMs were lower than 25 µm. A PEM based on a 50 µm PTFE film, with the wet thickness of 73 µm, was also prepared under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To enhance the stability of PEMs based on RX-PTFE, the concept of double cross-linking with the use of thin films was introduced. Hiraiwa et al prepared a cross-linked PEM by the RIG of St/DVB onto RX-PTFE of different thicknesses followed by sulfonation. Gas permeation experiments showed that thinner membranes (13.6 ± 0.5 μm) have higher gas crossover values than their thicker counterparts (73.8 ± 2.7 μm).…”
Section: Strategies To Enhance Stability Of Membranes For Low Tempera...mentioning
confidence: 99%
See 3 more Smart Citations
“…To enhance the stability of PEMs based on RX-PTFE, the concept of double cross-linking with the use of thin films was introduced. Hiraiwa et al prepared a cross-linked PEM by the RIG of St/DVB onto RX-PTFE of different thicknesses followed by sulfonation. Gas permeation experiments showed that thinner membranes (13.6 ± 0.5 μm) have higher gas crossover values than their thicker counterparts (73.8 ± 2.7 μm).…”
Section: Strategies To Enhance Stability Of Membranes For Low Tempera...mentioning
confidence: 99%
“…Gas permeation experiments showed that thinner membranes (13.6 ± 0.5 μm) have higher gas crossover values than their thicker counterparts (73.8 ± 2.7 μm). A maximum power density of 469 mW cm –2 was obtained for a MEA based on a 18.6 ± 1.3 μm thick PEM with a DG of 38.3% at 60 °C and a relative humidity of 16% …”
Section: Strategies To Enhance Stability Of Membranes For Low Tempera...mentioning
confidence: 99%
See 2 more Smart Citations